Effect of Plantago major L. seed mucilage on physicochemical, rheological, textural and sensory properties of non-fat yogurt - Mojtaba Yousefi; Elham Khanniri; Nasim Khorshidian (Applied Food Research)
Seed mucilages are water-soluble polysaccharides that can be used as gelling agents, stabilizers, emulsifiers, and coatings in the food industry. The aim of the present study was to evaluate the effect of Plantago major L. seed mucilage (PSM) at different levels (1, 3, and 5 % w/v) on quality and sensory properties of non-fat yogurt during refrigerated storage for 21 days. The results revealed a significant decrease in pH (increase in acidity) by adding PSM. Fortified yogurts with different concentrations of PSM exhibited lower whey loss compared to plain yogurts, while storage time had an adverse effect. The apparent viscosity and dynamic moduli (Gʹ, Gʺ) of samples enhanced with increasing levels of PSM and they were higher in yogurts containing PSM. The addition of PSM decreased the adhesiveness and increased the hardness, cohesiveness, gumminess, and springiness of yogurts. Evaluation of sensory properties demonstrated that the treatments containing 5 % PSM received the highest scores regarding taste, mouthfeel, appearance, and overall acceptability, which showed significant differences compared to other yogurt samples (p<0.05). It can be concluded that PSM at a concentration of 5 % is a good choice to improve the characteristics of non-fat yogurt which can be of practical use in industrial production.